Usability of Electrical E-Wiring Module Using Mobile Apps - Ibrahim, Abu Bakar; Ariffin, Shamsul Arrieya; Abas, Ashardi; Misbah, Mohamad Fahim (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2020)
In education, the use of smart-phone apps is very helpful in the process of teaching and learning. Therefore, this situation inspires and opportunities for the development of a smart-phone app namely the Electrical e-Wiring Module (called, MePE). The MePE app is a smart-phone app or mobile apps developed to help students who are taking electrical wiring courses to refer how to learn electrical wiring via smart-phone applications. In addition, this application can also be used as a teaching tool in the process of learning electrical wiring. The study was conducted to identify the requirements for MePE app, develops and tests the functionality of MePE app. There are four main sections in this application. This application is developed in accordance with the evolutionary prototype methodology. As a result of the functionality testing performed on the nine functions available on the MePE app all the functions passed the tests that have been performed. In addition, 24 of 31 respondents agreed that the MePE application is helpful and effective in learning electrical wiring. It is hoped that with this application it will help students that study electrical wiring courses to make reference to electrical wiring through this application.